Surface paleosols of the loess island within Moscow glacial limits: Vladimir Opolie. (16th April 2015) - Makeev, Alexander; Kulinskaya, Elena; Yakusheva, Tatiana
Abstract: Vladimir Opolie is a typical loess island with soil pattern that differs strikingly from that of adjacent territories. Soils are characterized by a controversial set of features. They have common features with other loess islands located in various environmental zones (similar dependence on microtopography with second humus horizons in soils within depressions and accumulation of carbonates in soils on the main surfaces). On the other hand they differ from soils of loess islands formed on typical loess due to specific features of sediments: mantle loams, and a northern variety of loess. A pedostratigraphic approach to the study of soils of Vladimir Opolye reveals that constitution of the upper loess strata depends on paleocryogenic microtopography and that relict soil features (second humus horizon, pattern of carbonates distribution) are syngenetic with the final stages of loess sedimentation. The abundance of relict features indicates that the soils of Vladimir Opolie are surface paleosols.